Composition, ionic gel coating as well as preparation method and application of ionic gel coating

By combining fluoropolyimide, ionic liquid, surfactant and additives in the material, forming a highly hydrophobic ionic gel coating, the ice adhesion strength of existing anti-ice materials in low temperature environments and The problem of insufficient durability has achieved improvements in low ice adhesion performance and versatility.

CN119264808AActive Publication Date: 2025-01-07TSINGHUA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411121550.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-01-07
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The existing anti-icing/de-icing materials and technologies have problems such as high cost, high complexity, uneco-friendly and poor stability in extreme climates, especially in low temperature environments with insufficient ice adhesion strength and long-term durability.

Method used

Using a composition including fluoropolyimide, low-cooling point non-volatile ionic liquid, surfactant and additive, the ionic liquid is locked through various forces such as hydrogen bonding and electrostatic action to form high hydrophobicity and transparency. and versatile ionic gel coating, combined with substrate surface for self-healing and self-cleaning, reducing ice adhesion strength and improving robustness.

Benefits of technology

It significantly reduces ice adhesion strength in extremely low temperature environments, improves the robustness of low ice adhesion properties of the material, and has room temperature self-healing and self-cleaning functions, suitable for anti-icing in industrial facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264808A_ABST
    Figure CN119264808A_ABST
Patent Text Reader

Abstract

The invention provides a composition, an ionic gel coating and a preparation method and application thereof, the composition contains fluorine-containing polyamide acid, ionic liquid, a surfactant and an additive, and the mass ratio of the fluorine-containing polyamide acid to the ionic liquid to the surfactant to the additive is (20-60): (1.5-27): 1: (40-60). According to the composition disclosed by the invention, the ionic liquid with low condensation point, non-volatility and chemical stability is locked in the fluorine-containing polyimide with high and low temperature resistance and excellent mechanical properties, and the surface active agent and the additive are coupled with the fluorine-containing polyimide, so that the whole material has relatively high hydrophobicity and transparency; and meanwhile, the coating has multiple functions of room-temperature self-repairing, self-cleaning and the like, has relatively high binding force with the surface of a base material such as stainless steel and the like, and can reduce the ice adhesion strength of the surface to a great extent and improve the robustness of the low ice adhesion performance of the material in an extremely low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional materials, and in particular to a composition, an ion gel coating, and a preparation method and application thereof. Background Art

[0002] Icing has a very adverse impact on industrial facilities including transportation systems, telecommunication systems, and energy systems, often causing catastrophic safety problems and huge economic losses.

[0003] Current anti-icing / de-icing strategies mainly include active and passive methods. Active de-icing mainly includes active ice melting and de-icing achieved by using traditional chemical agents (melting agents), thermal forces (steam heating and electric heating ice melting), mechanical forces (mechanical vibration) and other methods. However, this active de-icing strategy is often accompanied by high costs and complex system designs, and many methods are considered to be environmentally unfriendly.

[0004] On this basis, in the past decade, zero-energy passive anti-icing / de-icing materials and surfaces have received great attention. Various means are used to construct materials and surfaces that can repel water droplets, inhibit ice formation, and reduce ice adhesion to prevent ice formation. These means mainly include the following three methods:

[0005] (1) Superhydrophobic structure or coating; Combined with the various stages of the freezing process, the supercooled droplets first wet the solid surface and then quickly freeze into ice. In this case, the superhydrophobic surface can be called an ideal anti-icing surface: on the one hand, it can remove the supercooled droplets by simply tilting the surface, the droplets bouncing off the surface, etc., reducing the probability of nucleation on the surface; on the other hand, the heat transfer between the coating surface and the supercooled droplets is significantly inhibited, thereby reducing the freezing temperature and delaying the freezing time. However, most of the current superhydrophobic coatings are brittle, and due to the low adhesion of low surface energy materials, they are susceptible to various mechanical damages such as peeling, wear, and dynamic impact, and the preparation process is generally more complicated and cannot meet the strict requirements of industrial applications. In addition, the defect of this interface is that it will form a high-energy solid-liquid interface. At low temperatures, this interface will promote the heterogeneous nucleation of ice, destroy the air pockets in the structure, and then lead to higher ice adhesion strength, and it has the defects of easy damage to the microstructure and insufficient stability.

[0006] (2) Using hygroscopic polymers to prepare highly hydratable ice-repellent coatings and hydrogels. The water-containing lubricating layer can significantly reduce the adhesion of ice, thereby inhibiting ice accumulation under wind. However, the preparation process of such coatings or gels is relatively complicated and they are easily damaged in humid or other extreme climates.

[0007] (3) Smooth liquid injected into porous surfaces. For example, researchers have developed a series of smooth porous surfaces and waxy organic gels injected with lubricants by imitating the smooth leaves of terrestrial plants (such as pitcher plants). These materials can significantly reduce the adhesion of ice, so that the attached ice can be easily separated by gravity or airflow. However, this method faces the problem that the injected lubricant is extremely easy to migrate, evaporate or leak, resulting in the durability of liquid injected into smooth surfaces. On the other hand, the disadvantages of this method, such as high cost, easy damage due to mechanical wear or multiple icing / de-icing cycles, and the need for frequent maintenance and re-oiling, limit its practical application.

[0008] Therefore, it is an urgent problem to develop low-interface toughness material surfaces with low preparation cost, simple preparation process and coupled multifunctional properties to improve their adaptability to low-temperature environments and long-term durability (for example, the ability to maintain low ice adhesion properties). Summary of the invention

[0009] In view of this, one object of the present application is to provide a composition for ion gel coating, which can lock ionic liquid with low freezing point, non-volatility and chemical stability in fluorinated polyimide with high and low temperature resistance and excellent mechanical properties through various forces such as hydrogen bonding and electrostatic action, and couple it with surfactants and additives to make the material as a whole have high hydrophobicity and transparency, and at the same time have multiple functions such as room temperature self-repair and self-cleaning, and have high bonding force with the surface of substrate (such as Al, GCr15, stainless steel, silicon wafer, glass wafer, etc.), which can greatly reduce the ice adhesion strength of the surface in extreme low temperature environment and improve the robustness of the material's low ice adhesion performance.

[0010] Another object of the present application is to provide a method for preparing the composition.

[0011] Another object of the present application is to provide an ion gel coating.

[0012] Another object of the present application is to provide a method for preparing an ion gel coating.

[0013] Another object of the present application is to provide a use of an ion gel coating.

[0014] To achieve the above objectives, the present application proposes a composition in a first aspect, comprising a fluorine-containing polyamic acid, an ionic liquid, a surfactant and an additive.

[0015] In some embodiments, the mass ratio of the fluorinated polyamic acid, the ionic liquid, the surfactant and the additive is (20-60):(1.5-27):1:(40-60).

[0016] In some embodiments, the fluorine-containing polyamic acid includes at least one of a compound having a structure shown in Formula 1, a compound having a structure shown in Formula 2, and a compound having a structure shown in Formula 3:

[0017]

[0018]

[0019] Wherein, a, b and c are the numbers of repeating units in the compound of the structure shown in Formula 1, the compound of the structure shown in Formula 2 and the compound of the structure shown in Formula 3, respectively.

[0020] In some embodiments, the number average molecular weight of the compound represented by Formula 1, the compound represented by Formula 2, and the compound represented by Formula 3 are all 20,000-30,000, including but not limited to 20,000, 22,500, 25,000, 27,500 or 30,000.

[0021] In some embodiments, the viscosity of the fluorinated polyamic acid is 0.1-2 Pa·s.

[0022] In some embodiments, the ionic liquid includes but is not limited to at least one of imidazolium chloride, imidazolium tetrafluoroborate, imidazolium bis(trifluoromethanesulfonyl)imide, imidazolium trifluoromethanesulfonate, imidazolium acetate, imidazolium hexafluorophosphate, etc., preferably 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0023] In some embodiments, the surfactant includes but is not limited to at least one of dodecyl dimethyl ammonium bromide, hexadecyl dimethyl ammonium bromide, 1-dodecyl-2,3-dimethyl imidazolium bromide, etc., preferably dodecyl dimethyl ammonium bromide.

[0024] In some embodiments, the additive includes but is not limited to at least one of octavinyl-cage polysilsesquioxane, aniline propyl cage polysilsesquioxane, dodecaphenyl cage polysilsesquioxane, etc., preferably aniline propyl cage polysilsesquioxane.

[0025] The second aspect of the present application provides a method for preparing a composition, comprising:

[0026] The fluorinated polyamic acid and the ionic liquid are first mixed to obtain a mixed solution;

[0027] The mixed solution, the surfactant and the additive are mixed for a second time to obtain the composition.

[0028] In some embodiments, the method for preparing the composition further comprises the step of preparing the fluorinated polyamic acid; the method for preparing the fluorinated polyamic acid comprises:

[0029] The fluorine-containing polyamic acid is obtained by reacting 2,2′-bis(trifluoromethyl)benzidine with 4,4′-(hexafluoroisopropylidene)diphthalic anhydride in an organic solvent.

[0030] In some embodiments, the first mixing and the second mixing both include at least one of ultrasonic dispersion, stirring, and grinding.

[0031] The third aspect of the present application provides an ion gel coating, comprising the composition described in the present application or a composition prepared by the preparation method of the composition described in the present application; the fluorinated polyamic acid in the composition is cured to form a fluorinated polyimide.

[0032] In some embodiments, the fluorinated polyimide includes at least one of a compound having a structure shown in Formula 4, a compound having a structure shown in Formula 5, and a compound having a structure shown in Formula 6:

[0033]

[0034] Wherein, n, m and k are the numbers of repeating units in the compound of the structure shown in Formula 4, the compound of the structure shown in Formula 5 and the compound of the structure shown in Formula 6, respectively.

[0035] In some embodiments, the number average molecular weight of the compound represented by Formula 4, the compound represented by Formula 5, and the compound represented by Formula 6 are all 10,000-30,000.

[0036] In some embodiments, the contact angle of the ion gel coating to water is 111-121°.

[0037] The fourth aspect of the present application provides a method for preparing an ion gel coating, comprising:

[0038] The composition is dripped or coated on the surface of a substrate and then dried to obtain the ion gel coating.

[0039] In some embodiments, when the composition is dropped onto the surface of a substrate, the method for preparing an ion gel coating further comprises a step of allowing the composition to flow naturally before drying.

[0040] In some embodiments, the method for preparing the ion gel coating further comprises the step of sandblasting or frosting the surface of the substrate before dripping or coating the composition on the surface of the substrate.

[0041] In some embodiments, the substrate comprises a material suitable for surface blasting.

[0042] In some embodiments, the drying method includes gradient temperature drying under vacuum conditions.

[0043] In some embodiments, after the drying, the fluorinated polyamic acid is cured to become the fluorinated polyimide.

[0044] The fifth aspect of the present application relates to the use of the ion gel coating described in the present application as an anti-icing surface, or the use of the ion gel coating prepared by the preparation method of the ion gel coating described in the present application as an anti-icing surface.

[0045] The composition described in this application can at least bring the following beneficial effects:

[0046] The ion gel coating can lock the ionic liquid with low freezing point, non-volatility and chemical stability in the fluorinated polyimide with high and low temperature resistance and excellent mechanical properties through various forces such as hydrogen bonding and electrostatic action, and couple it with surfactants and additives to make the material as a whole have high hydrophobicity and transparency. At the same time, it has multiple functions such as room temperature self-repair and self-cleaning, and has a high bonding force with the surface of the substrate (such as Al, GCr15, stainless steel, silicon wafer, glass wafer, etc.), which can greatly reduce the surface ice adhesion strength and improve the robustness of the material's low ice adhesion performance in extremely low temperature environments (for example, below -60°C, preferably -80°C to -60°C).

[0047] Specifically, the mechanism for achieving the above beneficial effects is as follows:

[0048] Due to the high electronegativity of fluorine atoms and low intermolecular interactions in polyimides containing fluorine groups, the hydrogen atoms on the imidazolium cations in ionic liquids and long-chain cations in surfactants such as dodecyldimethylammonium bromide (DDAB) may form hydrogen bonds with fluorine atoms or imide groups on polyimide molecules; the cations and anions of ionic liquids can form strong ion-dipole interactions (electrostatic interactions) with polar groups (such as imide groups) in polyimides; among them, the surfactants DDAB and the like interact with ionic liquids mainly through electrostatic interactions (DDAB is a quaternary ammonium salt with a positive charge. Ionic liquids contain negatively charged anions. The electrostatic attraction between positive and negative charges can cause DDAB and the like to form strong electrostatic interactions with anions in ionic liquids), ion-dipole interactions, and electrostatic interactions between ionic liquids and surfactants. The surfactants such as DDAB can form a stable system in the ionic liquid through interactions (the cationic part of surfactants such as DDAB can produce ion-dipole interactions with imidazolium cations and anions in the ionic liquid. This interaction can enhance the compatibility between the two), hydrophobic interactions (surfactants such as DDAB have long-chain alkyl groups and have significant hydrophobicity. The imidazolium cations and anions in the ionic liquid have certain hydrophobicity, especially the fluorinated groups of the anions. The interactions between these hydrophobic groups help to form hydrophobic interactions, thereby stabilizing the mixed system of the two). Among them, the additives such as octavinyl-cage polysilsesquioxane (8-POSS) mainly give the composition an excellent and long-lasting hydrophobic state by concentrating the siloxy groups on the surface.

[0049] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.

[0051] in:

[0052] Figure 1 : are comparative photos of the ion gel coatings prepared in Example 4, Example 1 and Example 5, wherein:

[0053] a is a photograph of the ion gel coating prepared in Example 4,

[0054] b is a photo of the ion gel coating prepared in Example 1,

[0055] c is a photograph of the ion gel coating prepared in Example 5.

[0056] Figure 2The following is a comparison chart of the interfacial hydrophobicity of the coatings prepared in Comparative Example 3 and Example 1, wherein:

[0057] The F_PAA-ILs coating is the coating prepared in Comparative Example 3 (left side);

[0058] The ion gel coating is the coating prepared in Example 1 (right side);

[0059] WCA stands for contact angle.

[0060] Figure 3a Schematic diagram of the structure of the homemade ice adhesion strength testing device.

[0061] Figure 3b Figure 2 shows the temperature variation during the ice adhesion strength and long-term robustness tests.

[0062] Figure 4 It is a comparison chart of the anti-ice adhesion strength of the substrates or coatings of Comparative Example 1, Comparative Example 2 and Example 1.

[0063] Figure 5 It is a comparison chart of the anti-ice adhesion strength of the substrates or coatings of Comparative Example 7, Comparative Example 8 and Example 2.

[0064] Figure 6 It is a comparison chart of the anti-ice adhesion strength of the substrates or coatings of Comparative Example 9, Comparative Example 10 and Example 3.

[0065] Figure 7 This is a comparison chart of the robustness of low ice adhesion performance of the coatings prepared in Comparative Example 3 and Example 3.

[0066] Figure 8 This is a self-healing performance effect diagram of the ion gel coating prepared in Example 1, wherein:

[0067] d is a state diagram with a scratch on the coating surface at a magnification of 300 times;

[0068] e is the repair state of the surface scratches after the coating was placed at 25°C for 3 hours at a magnification of 300 times;

[0069] f is a state diagram with a magnification of 500 times when there are scratches on the coating surface;

[0070] g is a diagram showing the repair status of surface scratches at a magnification of 500 times after the coating was placed at 25°C for 3 hours.

[0071] Fig. 9 This is a self-cleaning performance effect diagram of the ion gel coating prepared in Example 1, wherein:

[0072] h is the initial state diagram of hydrophilic dust on the coating surface;

[0073] i is a state diagram of water dripping on the coating surface with hydrophilic dust;

[0074] j is a diagram showing the cleaning state after water is dripped on the coating surface with hydrophilic dust for a period of time;

[0075] k is the initial state diagram of hydrophobic dust on the coating surface;

[0076] m is the state diagram of water dripping on the coating surface with hydrophobic dust;

[0077] n is a diagram showing the cleaning status after water is dripped on the coating surface with hydrophobic dust for a period of time.

[0078] Reference numerals:

[0079] 1-environmental temperature control cabinet; 2-sample; 3-icing icicle model; 4-stepping push rod; 5-cooling table; 6-driving unit. DETAILED DESCRIPTION

[0080] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0081] In this application, the disclosure of numerical ranges includes all values ​​within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.

[0082] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0083] <Composition>

[0084] The composition of the embodiment of the present application includes fluorine-containing polyamic acid, ionic liquid, surfactant and additives.

[0085] In some embodiments, the mass ratio of fluorinated polyamic acid, ionic liquid, surfactant and additive is (20-60): (1.5-27): 1: (40-60). In the embodiments of the present application, the mass ratio of fluorinated polyamic acid, ionic liquid, surfactant and additive is within the above range, which can achieve a hydrophobic state with the highest water contact angle and a low ice adhesion strength with high robustness; if it exceeds the above range, it may cause the hydrophobic state of the interface to deteriorate and the ice adhesion strength to increase. For example, when the content of ionic liquid is too high, it may result in the inability to solidify and form due to the high liquid component (ionic liquid), thereby forming a usable and testable coating. When the content of ionic liquid is too low, it is impossible to form a coating with low interface toughness due to the low liquid component (ionic liquid), that is, the ice adhesion strength will be greatly improved. When the content of surfactants such as DDAB is too high, the contact angle of the coating decreases due to the amphiphilicity of DDAB and other substances, and a good hydrophobic state cannot be achieved; when the content of additives such as 8-POSS is too high, although the interfacial hydrophobicity will be further improved, the ice adhesion strength of the coating will also increase further. When the content of surfactants such as DDAB is too low, the internal ionic liquid cannot be more evenly distributed in the fluorinated polyamic acid matrix; when the content of additives such as 8-POSS is too low, the contact angle of the coating decreases, and a good hydrophobic state cannot be achieved.

[0086] In some embodiments, the fluorinated polyamic acid includes at least one of a compound having a structure shown in Formula 1, a compound having a structure shown in Formula 2, and a compound having a structure shown in Formula 3:

[0087]

[0088] Wherein, a, b and c are the numbers of repeating units in the compound of the structure shown in Formula 1, the compound of the structure shown in Formula 2 and the compound of the structure shown in Formula 3, respectively.

[0089] In some embodiments, the number average molecular weight of the compound represented by Formula 1, the compound represented by Formula 2, and the compound represented by Formula 3 are all 20,000-30,000, including but not limited to 20,000, 22,500, 25,000, 27,500 or 30,000.

[0090] It should be noted that the compound with the structure shown in the above formula 1 corresponds to the situation of Example 1 later in this application, the compound with the structure shown in the above formula 2 corresponds to the situation of Example 2 later in this application, and the compound with the structure shown in the above formula 3 corresponds to the situation of Examples 3 and 10 later in this application.

[0091] In some embodiments, the viscosity of the fluorinated polyamic acid is 0.1-2 Pa·s, including but not limited to 0.1 Pa·s, 0.5 Pa·s, 1 Pa·s, 1.5 Pa·s or 2 Pa·s.

[0092] In some embodiments, the fluorinated polyamic acid is in the form of a fluorinated polyamic acid solution.

[0093] Exemplarily, the solid content of the fluorinated polyamic acid solution is 15-20 wt %, and the solvent includes but is not limited to at least one of dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and the like.

[0094] In some embodiments, the ionic liquid includes but is not limited to at least one of imidazolium chloride, imidazolium tetrafluoroborate, imidazolium bis(trifluoromethanesulfonyl)imide, imidazolium trifluoromethanesulfonate (CAS: 29727-06-8), imidazolium acetate, imidazolium hexafluorophosphate, and the like.

[0095] Exemplary, imidazolium chloride salts include, but are not limited to, at least one of 1-ethyl-2,3-dimethylimidazolium chloride salt (CAS: 92507-97-6), 1-octyl-3-methylimidazolium chloride salt (CAS: 64697-40-1), 1-butyl-3-methylimidazolium chloride salt (CAS: 79917-90-1), 1-ethyl-3-methylimidazolium chloride salt (CAS: 65039-09-0) or 1-dodecyl-3-methylimidazolium chloride salt (CAS: 114569-84-5).

[0096] Exemplary, imidazole tetrafluoroborate includes, but is not limited to, at least one of 1-propyl-3-methylimidazolium tetrafluoroborate (CAS: 244193-48-4), 1-butyl-3-methylimidazolium tetrafluoroborate (CAS: 174501-65-6), 1-ethyl-3-methylimidazolium tetrafluoroborate (CAS: 143314-16-3), 1-methylimidazolium tetrafluoroborate (CAS: 151200-14-5) or 1-octyl-3-methylimidazolium tetrafluoroborate (CAS: 244193-52-0), etc.

[0097] Exemplary, imidazole bis(trifluoromethanesulfonyl)imide salts include, but are not limited to, at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 174899-83-3), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 174899-82-2), 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 862731-66-6), 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 216299-72-8) or 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 174899-90-2).

[0098] Exemplary, imidazole acetates include, but are not limited to, at least one of 1-ethyl-3-methylimidazolium acetate (CAS: 143314-17-4), 1-butyl-3-methylimidazolium acetate (CAS: 284049-75-8), 1-octyl-3-methylimidazolium acetate (CAS: 366491-21-6), 1-methylimidazolium acetate (CAS: 616-47-7), or 1-propyl-3-methylimidazolium acetate (CAS: 1005328-08-4).

[0099] Exemplarily, the imidazole hexafluorophosphate includes, but is not limited to, at least one of 1-methylimidazolium hexafluorophosphate (CAS: 57367-08-5), 1-ethyl-3-methylimidazolium hexafluorophosphate (CAS: 155371-19-0), 1-propyl-3-methylimidazolium hexafluorophosphate (CAS: 216300-12-8), 1-butyl-3-methylimidazolium hexafluorophosphate (CAS: 174501-64-5), or 1-octyl-3-methylimidazolium hexafluorophosphate (CAS: 304680-36-2).

[0100] As a preferred example, the ionic liquid is 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C3mim][NTf2]).

[0101] In some embodiments, the surfactant includes but is not limited to at least one of dodecyldimethylammonium bromide, hexadecyldimethylammonium bromide, 1-dodecyl-2,3-dimethylimidazolium bromide, and the like.

[0102] As a preferred example, the surfactant is dodecyldimethylammonium bromide.

[0103] In some embodiments, the additive includes but is not limited to at least one of octavinyl-cage polysilsesquioxane (8-POSS), aniline propyl cage polysilsesquioxane (N-POSS), and dodecaphenyl cage polysilsesquioxane (N12-POSS).

[0104] As a preferred example, the additive is aniline propyl cage-type polysilsesquioxane (N-POSS), and more preferably aniline propyl cage-type polysilsesquioxane (N-POSS) with a particle size of 1-3 nm.

[0105] The composition of the embodiment of the present application can at least bring the following beneficial effects:

[0106] The ion gel coating can lock the ionic liquid with low freezing point, non-volatility and chemical stability in the fluorinated polyimide with high and low temperature resistance and excellent mechanical properties through various forces such as hydrogen bonding and electrostatic action, and couple it with surfactants and additives to make the material as a whole have high hydrophobicity and transparency. At the same time, it has multiple functions such as room temperature self-repair and self-cleaning, and has a high bonding force with the surface of the substrate (such as Al, GCr15, stainless steel, silicon wafer, glass wafer, etc.), which can greatly reduce the surface ice adhesion strength and improve the robustness of the material's low ice adhesion performance in extremely low temperature environments (for example, below -60°C, preferably -80°C to -60°C).

[0107] <Method for preparing composition>

[0108] The preparation method of the composition of the embodiment of the present application can be used to prepare the composition of the embodiment of the present application.

[0109] The preparation method of the composition of the present application embodiment comprises the following steps:

[0110] S101, first mixing the fluorinated polyamic acid and the ionic liquid to obtain a mixed solution (F_PAA-ILs).

[0111] In some embodiments, the mixing mass ratio of the fluorinated polyamic acid and the ionic liquid is (20-60):(1.5-27), that is, the amount of the ionic liquid is 7.5-45 wt.% of the fluorinated polyamic acid.

[0112] Illustratively, the amount of the ionic liquid used is 7.5 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, 30 wt.%, 35 wt.%, 40 wt.%, or 45 wt.%, etc., of the fluorinated polyamic acid.

[0113] In some embodiments, the fluorinated polyamic acid includes at least one of a compound having a structure shown in Formula 1, a compound having a structure shown in Formula 2, and a compound having a structure shown in Formula 3:

[0114]

[0115] Wherein, a, b and c are the numbers of repeating units in the compound of the structure shown in Formula 1, the compound of the structure shown in Formula 2 and the compound of the structure shown in Formula 3, respectively.

[0116] In some embodiments, the number average molecular weight of the compound represented by Formula 1, the compound represented by Formula 2, and the compound represented by Formula 3 are all 20,000-30,000, including but not limited to 20,000, 22,500, 25,000, 27,500 or 30,000.

[0117] It should be noted that the compound with the structure shown in the above formula 1 corresponds to the situation of Example 1 later in this application, the compound with the structure shown in the above formula 2 corresponds to the situation of Example 2 later in this application, and the compound with the structure shown in the above formula 3 corresponds to the situation of Examples 3 and 10 later in this application.

[0118] In some embodiments, the viscosity of the fluorinated polyamic acid is 0.1-2 Pa·s, including but not limited to 0.1 Pa·s, 0.5 Pa·s, 1 Pa·s, 1.5 Pa·s or 2 Pa·s.

[0119] In some embodiments, the ionic liquid includes but is not limited to at least one of imidazolium chloride, imidazolium tetrafluoroborate, imidazolium bis(trifluoromethanesulfonyl)imide, imidazolium trifluoromethanesulfonate (CAS: 29727-06-8), imidazolium acetate, imidazolium hexafluorophosphate, and the like.

[0120] Exemplary, imidazolium chloride salts include, but are not limited to, at least one of 1-ethyl-2,3-dimethylimidazolium chloride salt (CAS: 92507-97-6), 1-octyl-3-methylimidazolium chloride salt (CAS: 64697-40-1), 1-butyl-3-methylimidazolium chloride salt (CAS: 79917-90-1), 1-ethyl-3-methylimidazolium chloride salt (CAS: 65039-09-0) or 1-dodecyl-3-methylimidazolium chloride salt (CAS: 114569-84-5).

[0121] Exemplary, imidazole tetrafluoroborate includes, but is not limited to, at least one of 1-propyl-3-methylimidazolium tetrafluoroborate (CAS: 244193-48-4), 1-butyl-3-methylimidazolium tetrafluoroborate (CAS: 174501-65-6), 1-ethyl-3-methylimidazolium tetrafluoroborate (CAS: 143314-16-3), 1-methylimidazolium tetrafluoroborate (CAS: 151200-14-5) or 1-octyl-3-methylimidazolium tetrafluoroborate (CAS: 244193-52-0), etc.

[0122] Exemplary, imidazole bis(trifluoromethanesulfonyl)imide salts include, but are not limited to, at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 174899-83-3), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 174899-82-2), 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 862731-66-6), 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 216299-72-8) or 1-ethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt (CAS: 174899-90-2).

[0123] Exemplary, imidazole acetates include, but are not limited to, at least one of 1-ethyl-3-methylimidazolium acetate (CAS: 143314-17-4), 1-butyl-3-methylimidazolium acetate (CAS: 284049-75-8), 1-octyl-3-methylimidazolium acetate (CAS: 366491-21-6), 1-methylimidazolium acetate (CAS: 616-47-7), or 1-propyl-3-methylimidazolium acetate (CAS: 1005328-08-4).

[0124] Exemplarily, the imidazole hexafluorophosphate includes, but is not limited to, at least one of 1-methylimidazolium hexafluorophosphate (CAS: 57367-08-5), 1-ethyl-3-methylimidazolium hexafluorophosphate (CAS: 155371-19-0), 1-propyl-3-methylimidazolium hexafluorophosphate (CAS: 216300-12-8), 1-butyl-3-methylimidazolium hexafluorophosphate (CAS: 174501-64-5), or 1-octyl-3-methylimidazolium hexafluorophosphate (CAS: 304680-36-2).

[0125] As a preferred example, the ionic liquid is 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C3mim][NTf2]).

[0126] Exemplarily, the first mixing method of the fluorine-containing polyamic acid and the ionic liquid includes, but is not limited to, at least one of stirring, ultrasonic dispersion, grinding, and the like.

[0127] It should be noted that in the embodiments of the present application, the fluorinated polyamic acid can be a commercially available product or can be homemade.

[0128] When the fluorine-containing polyamic acid needs to be prepared in-house, the preparation method of the composition of the embodiment of the present application further includes the step of preparing the fluorine-containing polyamic acid.

[0129] Exemplarily, the preparation methods of fluorine-containing polyamic acid include but are not limited to the following two methods: method 1 and method 2.

[0130] [Method 1]

[0131] The preparation method of fluorinated polyamic acid comprises the following steps:

[0132] 2,2′-bis(trifluoromethyl)benzidine (TFDB) and 4,4′-(hexafluoroisopropylidene) diphthalic anhydride (6FDA) are reacted in an organic solvent to obtain a fluorinated polyamic acid (F_PAA).

[0133] In some embodiments, the mass ratio of 2,2′-bis(trifluoromethyl)benzidine to 4,4′-(hexafluoroisopropylidene)diphthalic anhydride is (0.64-0.96):(0.56-0.84), including but not limited to 0.64:0.6, 0.64:0.7, 0.64:0.8, 0.96:0.7, 0.96:0.8, 0.8:0.7 or 0.8:0.84, etc.

[0134] As an optional example, the mass ratio of 2,2′-bis(trifluoromethyl)benzidine to 4,4′-(hexafluoroisopropylidene)diphthalic anhydride is 8:7.

[0135] In some embodiments, the amount of organic solvent used is generally 20-28 mL of organic solvent per gram of 2,2′-bis(trifluoromethyl)benzidine.

[0136] In some embodiments, the organic solvent includes, but is not limited to, at least one of dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and the like.

[0137] In some embodiments, the reaction is carried out under stirring conditions, and the stirring speed is not limited.

[0138] In some embodiments, the reaction temperature is between -5 and 0°C, including but not limited to -5°C, -4°C, -3°C, -2°C, -1°C or 0°C, etc.

[0139] In some embodiments, the reaction time is 2-6 hours, including but not limited to 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0140] As an optional example, the reaction temperature is -5°C and the reaction time is 4 hours.

[0141] As a preferred example, the preparation method of fluorinated polyamic acid comprises the following steps:

[0142] (1) The above organic solvent is added to 2,2′-bis(trifluoromethyl)benzidine (TFDB) and stirred until the solid powder is completely dissolved to obtain solution A.

[0143] (2) Add 4,4′-(hexafluoroisopropyl) diphthalic anhydride (6FDA) to solution A and continue stirring to react. When the viscosity of the solution begins to increase, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0144] In some embodiments, the criterion for observing the increase in solution adhesion in step (2) is that the viscosity is greater than QPa·s, and Q is 0.5-1.2, including but not limited to 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1 or 1.2, etc.

[0145] As an optional example, the criterion for observing the solution adhesion increase in step (2) is that the viscosity is greater than 0.5 Pa·s.

[0146] [Method 2]

[0147] In the embodiments of the present application, the preparation method of the fluorinated polyamic acid of method 2 is basically the same as that of method 1, except that: the 4,4′-(hexafluoroisopropyl) diphthalic anhydride (6FDA) in method 1 is replaced by biphenyltetracarboxylic dianhydride (BPDA), and the 2,2′-bis(trifluoromethyl)benzidine (TFDB) in method 1 is replaced by 4,4′-(trifluoromethyl)biphenyl diamine) (TFMB), and the addition order and addition ratio of 4,4′-(trifluoromethyl)biphenyl diamine) (TFMB) and biphenyltetracarboxylic dianhydride (BPDA) are changed.

[0148] In some embodiments, the mass ratio of biphenyltetracarboxylic dianhydride (BPDA) to 4,4'-(trifluoromethyl)benzenediamine) (TFMB) is 1:(0.7-0.9), including but not limited to 1:0.7, 1:0.8 or 1:0.9, etc., preferably 1:0.8.

[0149] Exemplarily, the preparation method of the fluorinated polyamic acid of method 2 comprises the following steps:

[0150] 1) Add the organic solvent to the biphenyltetracarboxylic dianhydride (BPDA) and continue stirring until the solid powder is completely dissolved to obtain solution B.

[0151] 2) Add 4,4'-(trifluoromethyl)benzenediamine) (TFMB) to solution B, continue stirring the reaction, and stop stirring when the adhesion of the solution begins to increase, to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0152] S102, performing a second mixing on the mixed solution, surfactant and additive obtained in step S101 to obtain a composition.

[0153] In some embodiments, the mass ratio of the fluorinated polyamic acid, the ionic liquid, the surfactant and the additive is (20-60): (1.5-27): 1: (40-60)

[0154] In some embodiments, the mass ratio of fluorinated polyamic acid to surfactant is 20:1 to 60:1, including but not limited to 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1 or 60:1, etc.

[0155] In some embodiments, the mass ratio of the fluorinated polyamic acid to the additive is 40:1 to 60:1, including but not limited to 40:1, 45:1, 50:1, 55:1 or 60:1, etc.

[0156] In some embodiments, the surfactant includes but is not limited to at least one of dodecyldimethylammonium bromide, hexadecyldimethylammonium bromide, 1-dodecyl-2,3-dimethylimidazolium bromide, and the like.

[0157] As a preferred example, the surfactant is dodecyldimethylammonium bromide.

[0158] In some embodiments, the additive includes at least one of octavinyl-cage polysilsesquioxane (8-POSS, also known as octavinylsilsesquioxane (CAS: 69655-76-1)), aniline propyl cage polysilsesquioxane (N-POSS, also known as aniline propyl cage polysilsesquioxane (CAS: 1708993-28-5)), and dodecaphenyl cage polysilsesquioxane (N12-POSS, CAS: 18923-59-6).

[0159] As a preferred example, the additive is aniline propyl cage-type polysilsesquioxane (N-POSS), and more preferably aniline propyl cage-type polysilsesquioxane (N-POSS) with a particle size of 1-3 nm.

[0160] In some embodiments, the second mixing method includes but is not limited to at least one of ultrasonic dispersion, stirring, grinding, etc.

[0161] As an optional example, the second mixing method is ultrasonic dispersion.

[0162] In some embodiments, the ultrasonic dispersion time is 2-4 h, including but not limited to 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0163] In some embodiments, the frequency of ultrasonic dispersion is 20-30 kHz, including but not limited to 20 kHz, 22.5 kHz, 25 kHz, 27.5 kHz or 30 kHz.

[0164] As an optional example, the above step S102 is: adding a surfactant and an additive to the mixed solution obtained in step S101 in sequence, and performing ultrasonic dispersion to obtain a colloidal liquid, that is, a composition.

[0165] <Ion gel coating>

[0166] The ion gel coating of the embodiment of the present application includes the composition of the embodiment of the present application, or a composition prepared by the preparation method of the composition of the embodiment of the present application; the fluorinated polyamic acid in the composition is cured to be a fluorinated polyimide.

[0167] In some embodiments, the fluorinated polyimide includes at least one of a compound having a structure shown in Formula 4, a compound having a structure shown in Formula 5, and a compound having a structure shown in Formula 6:

[0168]

[0169] Wherein, n, m and k are the numbers of repeating units in the compound of the structure shown in Formula 4, the compound of the structure shown in Formula 5 and the compound of the structure shown in Formula 6, respectively.

[0170] In some embodiments, the number average molecular weight of the compound represented by Formula 4, the compound represented by Formula 5, and the compound represented by Formula 6 is 10,000-30,000, including but not limited to 10,000, 15,000, 20,000, 25,000, or 30,000.

[0171] It should be noted that in the embodiments of the present application, the compound of the structure shown in Formula 4 is the product of the compound of the structure shown in the aforementioned Formula 1 after solidification, the compound of the structure shown in Formula 5 is the product of the compound of the structure shown in the aforementioned Formula 2 after solidification, and the compound of the structure shown in Formula 6 is the product of the compound of the structure shown in the aforementioned Formula 3 after solidification.

[0172] In some embodiments, the contact angle of the ion gel coating to water is 111-121°, including but not limited to 111°, 112°, 113°, 114°, 115°, 117°, 119° or 121°, etc.

[0173] In some embodiments, the transparency of the ion gel coating is 80-95%, including but not limited to 80%, 82.5%, 85%, 87.5%, 90%, 92.5% or 95%, etc.

[0174] It should be noted that in the embodiments of the present application, if there is no fluoropolyamic acid in the ion gel coating, it cannot be cured and formed.

[0175] The ion gel coating of the embodiment of the present application combines the low-temperature stability of fluorinated polyimide and ionic liquid, so that the gel coating has a lubricating effect, low freezing point performance and low interface toughness, which can greatly reduce the ice adhesion strength of the surface and maintain long-lasting low ice adhesion performance in an extremely low temperature environment (for example, below -60°C, preferably -80°C to -60°C). In addition, the coating has multifunctional properties such as high transparency, room temperature self-repairing, and self-cleaning, which is conducive to further improving the environmental adaptability of the ion gel coating.

[0176] <Method for preparing ion gel coating>

[0177] The method for preparing the ion gel coating of the embodiment of the present application can be used to prepare the ion gel coating of the embodiment of the present application.

[0178] The method for preparing the ion gel coating of the embodiment of the present application comprises the following steps:

[0179] The composition is dripped or coated on the surface of the substrate and then dried to obtain an ion gel coating.

[0180] It should be noted that the above composition is a composition of the embodiments of the present application, or a composition prepared by the preparation method of the composition of the embodiments of the present application.

[0181] In some embodiments, when the composition is dropped onto the surface of the substrate, the method for preparing the ion gel coating further comprises a step of allowing the composition to flow naturally before drying.

[0182] In some embodiments, the substrate comprises a material suitable for surface blasting.

[0183] Exemplarily, the substrate includes but is not limited to at least one of a fiberglass sheet, an Al sheet, GCr15, 304 stainless steel, a silicon sheet, and the like.

[0184] As a preferred example, the substrate is a glass fiber reinforced plastic sheet.

[0185] In some embodiments, the method for preparing the ion gel coating of the embodiment of the present application further includes the step of sandblasting or frosting the surface of the substrate before dripping or coating the composition on the surface of the substrate.

[0186] In the embodiments of the present application, the substrate is subjected to surface sandblasting or frosting treatment to ensure that the surface of the substrate achieves a roughness level of about 1-3 μm, thereby improving the adhesion of the coating to the substrate and having little effect on the properties of the coating surface itself.

[0187] In some embodiments, the drying method includes gradient temperature drying under vacuum conditions.

[0188] As an optional example, the drying method is gradient temperature drying under vacuum conditions.

[0189] Exemplarily, the gradient temperature drying under the above-mentioned vacuum conditions includes: in a vacuum drying oven, controlling the vacuum degree to be less than 0.06 MPa, maintaining a constant temperature at 40-50°C for 0.3-0.8 h, then maintaining a constant temperature at 70-90°C for 0.8-1.2 h, then maintaining a constant temperature at 110-130°C for 0.8-1.2 h, then maintaining a constant temperature at 140-160°C for 0.8-1.2 h, and finally maintaining a constant temperature at 170-190°C for 0.8-1.2 h.

[0190] In the embodiments of the present application, the drying method adopts gradient temperature drying under vacuum conditions, which can ensure that the dehydration condensation process of the fluorinated polyamic acid and the solvent volatilization process proceed smoothly, and ensure that the surface of the obtained coating is smooth and free of bubbles.

[0191] In some embodiments, after drying, the fluorinated polyamic acid is cured to form the fluorinated polyimide.

[0192] The preparation method of the ion gel coating of the embodiment of the present application mainly locks the ionic liquid in the fluorinated polyimide through various forces such as hydrogen bonding and electrostatic action, and couples it with various surfactants and additives to achieve controllable preparation of high-binding force and hydrophobic ion gel coating on the surface of general commonly used substrates (such as AL, GCr15, stainless steel, silicon wafers, glass wafers, etc.). The coating has multifunctional properties such as high transparency, room temperature self-repairing, and self-cleaning. It can achieve a great reduction in the ice adhesion strength of the surface and improve the robustness of the coating's low ice adhesion performance in extreme low temperature environments (for example, below -60°C, preferably -80°C to -60°C).

[0193] <Application of ion gel coating>

[0194] The ion gel coating of the embodiment of the present application or the ion gel coating prepared by the preparation method of the ion gel coating of the embodiment of the present application can be used as an anti-icing surface in industrial facilities including but not limited to transportation systems, telecommunication systems, energy systems, etc.

[0195] Exemplarily, the anti-icing surfaces include, but are not limited to, aircraft wings, ship decks, wind turbine blades, car windows, windshields, winter roads, etc.

[0196] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0197] 1. Examples and Comparative Examples

[0198] Example 1

[0199] (Method for preparing composition)

[0200] The preparation method of the composition of this embodiment comprises the following steps:

[0201] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -5°C at a speed of 200 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0202] (2) Add 1-propyl-3-methylimidazole di(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) at a mass ratio of 20 wt.% to the F_PAA obtained in step (1), and stir at a speed of 100 r / min for 15 min until the solution is completely mixed to obtain a F_PAA-ILs mixed solution.

[0203] (3) Add DDAB to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to surfactant dodecyldimethylammonium bromide (DDAB) of 40:1, further add anilinepropyl cage-type polysilsesquioxane (N-POSS) to the resulting solution at a mass ratio of F_PAA to additive N-POSS of 40:1, and ultrasonicate for 3 hours to uniformly disperse it into a colloidal liquid, the frequency of ultrasonication being 20 kHz, to obtain a F_PAA-ILs mixed solution containing a surfactant and an additive, i.e., the composition of this embodiment.

[0204] (Method for preparing ion gel coating)

[0205] The method for preparing the ion gel coating of this embodiment comprises the following steps:

[0206] Step 1: Select a fiberglass sheet with a size of 1.5 cm×1.5 cm×1 mm as a substrate, and perform frosting on the surface of the substrate so that the surface of the substrate has a roughness of about 3 μm.

[0207] Step 2: drip 0.5 g of the composition of this embodiment onto the surface of the substrate after frosting treatment in step 1, and allow it to flow naturally. Then, place it in a vacuum drying oven with a gradient temperature increase: control the vacuum degree to 0.03 MPa, keep the temperature at 50° C. for 0.5 h, keep the temperature at 80° C. for 1 h, keep the temperature at 120° C. for 1 h, keep the temperature at 150° C. for 1 h, and keep the temperature at 180° C. for 1 h to obtain the ion gel coating of this embodiment (such as Figure 2 shown).

[0208] Example 2

[0209] (Method for preparing composition)

[0210] The preparation method of the composition of this embodiment comprises the following steps:

[0211] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 30 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved. Then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -3°C at a speed of 300 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0212] (2) Add 1-propyl-3-methylimidazolium tetrafluoroborate (30 wt. %) to the F_PAA obtained in step (1), and stir at a speed of 100 r / min for 15 min until the solution is completely mixed to obtain a F_PAA-ILs mixed solution.

[0213] (3) C12MMImBr was added to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to surfactant 1-dodecyl-2,3-dimethylimidazolium bromide (C12MMImBr) of 20:1, and 8-POSS was further added to the resulting solution at a mass ratio of F_PAA to additive octavinyl-cage polysilsesquioxane (8-POSS) of 60:1, and ultrasonicated for 2 hours to uniformly disperse it into a colloidal liquid. The frequency of ultrasonic treatment was 20 kHz, and a F_PAA-ILs mixed solution containing a surfactant and an additive was obtained, which is the composition of this embodiment.

[0214] (Method for preparing ion gel coating)

[0215] The method for preparing the ion gel coating of this embodiment comprises the following steps:

[0216] Step 1: Select a mirror-finished Al sheet with a size of 1.5 cm×1.5 cm×1 mm as a substrate, and perform frosting on the surface of the substrate to make the surface of the substrate have a roughness of about 5 μm.

[0217] Step 2: Drop 0.6 g of the composition of this embodiment on the surface of the substrate after frosting in step 1 to allow it to level naturally, and then place it in a vacuum drying oven with a gradient temperature increase: control the vacuum degree to 0.04 MPa, keep the temperature at 50°C for 0.5 h, keep the temperature at 80°C for 1 h, keep the temperature at 120°C for 1 h, keep the temperature at 150°C for 1 h, and keep the temperature at 180°C for 1 h to obtain the ion gel coating of this embodiment.

[0218] Example 3

[0219] (Method for preparing composition)

[0220] The preparation method of the composition of this embodiment comprises the following steps:

[0221] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir at 0°C until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at 400 r / min for 3 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0222] (2) Add 45 wt.% of ionic liquid 1-propyl-3-methylimidazole di(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) to the F_PAA obtained in step (1), and stir at a speed of 100 r / min for 15 min until the solution is completely mixed to obtain a F_PAA-ILs mixed solution.

[0223] (3) Add DDAB to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to surfactant dodecyldimethylammonium bromide (DDAB) of 40:1, further add dodecaphenyl cage-type polysilsesquioxane (N12-POSS) to the resulting solution at a mass ratio of F_PAA to additive N12-POSS of 40:1, and ultrasonicate for 4 hours to disperse it evenly into a colloidal liquid, the frequency of ultrasonication being 20 kHz, to obtain a F_PAA-ILs mixed solution containing a surfactant and an additive, i.e., the composition of this embodiment.

[0224] (Method for preparing ion gel coating)

[0225] The method for preparing the ion gel coating of this embodiment comprises the following steps:

[0226] Step 1: Select a silicon wafer with a size of 1.5 cm×1.5 cm×1 mm as a substrate, and perform frosting on the surface of the substrate so that the surface of the substrate has a roughness of about 2 μm.

[0227] Step 2: Drop 0.7 g of the composition of this embodiment on the surface of the substrate after frosting in step 1 to allow it to flow naturally, and then place it in a vacuum drying oven with a gradient temperature increase: control the vacuum degree to 0.05 MPa, keep the temperature at 50°C for 0.5 h, keep the temperature at 80°C for 1 h, keep the temperature at 120°C for 1 h, keep the temperature at 150°C for 1 h, and keep the temperature at 180°C for 1 h to obtain the ion gel coating of this embodiment (as shown in FIG. 3 ).

[0228] Example 4 (lower limit of ionic liquid dosage, other aspects are the same as Example 1)

[0229] This embodiment is basically the same as Embodiment 1, except that:

[0230] In step (2), the amount of 1-propyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) added is 7.5% of the mass of F_PAA.

[0231] The ion gel coating of this embodiment is prepared as follows Figure 1 shown.

[0232] Example 5 (Upper limit of ionic liquid dosage, other aspects are the same as Example 1)

[0233] This embodiment is basically the same as Embodiment 1, except that:

[0234] In step (2), the amount of 1-propyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) added is 45% of the mass of F_PAA.

[0235] The ion gel coating of this embodiment is shown in FIG3 .

[0236] Example 6 (lower limit of surfactant dosage, other details are the same as in Example 1)

[0237] This embodiment is basically the same as Embodiment 1, except that:

[0238] In step (3), DDAB is added to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to surfactant dodecyl dimethyl ammonium bromide (DDAB) of 20:1.

[0239] Example 7 (Upper limit of surfactant dosage, other details are the same as in Example 1)

[0240] This embodiment is basically the same as Embodiment 1, except that:

[0241] In step (3), DDAB is added to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to surfactant dodecyl dimethyl ammonium bromide (DDAB) of 60:1.

[0242] Example 8 (intermediate dosage of additives)

[0243] This embodiment is basically the same as Embodiment 1, except that:

[0244] In step (3), aniline propyl cage-type polysilsesquioxane (N-POSS) is further added to the obtained solution at a mass ratio of F_PAA to the additive N-POSS of 50:1.

[0245] Example 9 (Upper limit of additive dosage)

[0246] This embodiment is basically the same as Embodiment 1, except that:

[0247] In step (3), aniline propyl cage-type polysilsesquioxane (N-POSS) is further added to the obtained solution in a mass ratio of F_PAA to the additive N-POSS of 60:1.

[0248] Example 10 (fluorinated polyamic acid is different from Example 1, and the rest is the same as Example 1)

[0249] This embodiment is basically the same as Embodiment 1, except that:

[0250] Step (1) is: weigh 1.0 g of biphenyltetracarboxylic acid dianhydride (BPDA) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) thereto, stir until the solid powder is completely dissolved, then add 0.8 g of 4,4'-(trifluoromethyl)benzenediamine) (TFMB) thereto, continue stirring and react at -5°C at a speed of 200 r / min for 4 hours, and when it is observed that the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0251] Comparative Example 1

[0252] This comparative example is a fiberglass sheet of Example 1 having a size of 1.5 cm×1.5 cm×1 mm and not subjected to frosting treatment.

[0253] Comparative Example 2 (the coating of Example 1 does not contain ionic liquid, surfactant and additive)

[0254] The preparation method of the coating of this comparative example comprises the following steps:

[0255] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -5°C at a speed of 200 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0256] (2) A glass fiber reinforced plastic sheet with a size of 1.5 cm×1.5 cm×1 mm is selected as the substrate, and the surface of the substrate is frosted so that the surface of the substrate has a roughness of about 3 μm.

[0257] (3) 0.5 g of the F_PAA obtained in step (1) was dropped onto the surface of the substrate after frosting treatment in step (2) to allow it to flow naturally, and then placed in a vacuum drying oven with a gradient temperature increase: the vacuum degree was controlled to be 0.03 MPa, the constant temperature was 50° C. for 0.5 h, the constant temperature was 80° C. for 1 h, the constant temperature was 120° C. for 1 h, the constant temperature was 150° C. for 1 h, and the constant temperature was 180° C. for 1 h to obtain the coating of this comparative example (glass fiber reinforced plastic sheet-F_PAA coating).

[0258] Comparative Example 3 (the coating of Example 1 does not contain surfactant and additives)

[0259] The preparation method of the coating of this comparative example comprises the following steps:

[0260] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -5°C at a speed of 200 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0261] (2) Add 1-propyl-3-methylimidazole di(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) at a mass ratio of 20 wt.% to the F_PAA obtained in step (1), and stir at a speed of 100 r / min for 15 min until the solution is completely mixed to obtain a F_PAA-ILs mixed solution.

[0262] (3) A glass fiber reinforced plastic sheet with a size of 1.5 cm×1.5 cm×1 mm is selected as the substrate, and the surface of the substrate is frosted so that the surface of the substrate has a roughness of about 3 μm.

[0263] (4) 0.5 g of the F_PAA-ILs mixed solution obtained in step (2) was dropped onto the surface of the substrate after frosting treatment in step (3) to allow it to flow naturally, and then placed in a vacuum drying oven with a gradient temperature increase: the vacuum degree was controlled to be 0.03 MPa, the constant temperature was 50°C for 0.5 h, the constant temperature was 80°C for 1 h, the constant temperature was 120°C for 1 h, the constant temperature was 150°C for 1 h, and the constant temperature was 180°C for 1 h to obtain the coating of this comparative example (F_PAA-ILs coating).

[0264] Comparative Example 4 (the coating of Example 1 does not contain additives)

[0265] The preparation method of the coating of this comparative example comprises the following steps:

[0266] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -5°C at a speed of 200 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0267] (2) Add 1-propyl-3-methylimidazole di(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) at a mass ratio of 20 wt.% to the F_PAA obtained in step (1), and stir at a speed of 100 r / min for 15 min until the solution is completely mixed to obtain a F_PAA-ILs mixed solution.

[0268] (3) Add DDAB to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to surfactant DDAB of 40:1, and ultrasonicate for 3 h to uniformly disperse it into a colloidal liquid. The frequency of ultrasonication is 20 kHz to obtain a F_PAA-ILs mixed solution containing a surfactant.

[0269] (4) A glass fiber reinforced plastic sheet with a size of 1.5 cm×1.5 cm×1 mm is selected as the substrate, and the surface of the substrate is frosted so that the surface of the substrate has a roughness of about 3 μm.

[0270] (5) 0.5 g of the F_PAA-ILs mixed solution containing a surfactant obtained in step (3) was dropped onto the surface of the substrate after frosting treatment in step (4) to allow it to flow naturally, and then placed in a vacuum drying oven with a gradient temperature increase: the vacuum degree was controlled to be 0.03 MPa, the constant temperature was 50°C for 0.5 h, the constant temperature was 80°C for 1 h, the constant temperature was 120°C for 1 h, the constant temperature was 150°C for 1 h, and the constant temperature was 180°C for 1 h to obtain the coating of this comparative example (F_PAA-ILs coating containing a surfactant).

[0271] Comparative Example 5 (the coating of Example 1 does not contain a surfactant)

[0272] The preparation method of the coating of this comparative example comprises the following steps:

[0273] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -5°C at a speed of 200 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0274] (2) Add 1-propyl-3-methylimidazole di(trifluoromethylsulfonyl)imide ([C3mim][NTf2]) at a mass ratio of 20 wt.% to the F_PAA obtained in step (1), and stir at a speed of 100 r / min for 15 min until the solution is completely mixed to obtain a F_PAA-ILs mixed solution.

[0275] (3) Add aniline propyl cage-type polysilsesquioxane (N-POSS) to the F_PAA-ILs solution obtained in step (2) at a mass ratio of F_PAA to additive N-POSS of 40:1, and ultrasonicate for 3 h to uniformly disperse it into a colloidal liquid. The frequency of ultrasonication is 20 kHz to obtain a F_PAA-ILs mixed solution containing the additive.

[0276] (4) A glass fiber reinforced plastic sheet with a size of 1.5 cm×1.5 cm×1 mm is selected as the substrate, and the surface of the substrate is frosted so that the surface of the substrate has a roughness of about 3 μm.

[0277] (5) 0.5 g of the F_PAA-ILs mixed solution containing additives obtained in step (3) was dropped onto the surface of the substrate after frosting treatment in step (4) to allow it to flow naturally, and then placed in a vacuum drying oven with a gradient temperature increase: the vacuum degree was controlled to be 0.03 MPa, the constant temperature was 50°C for 0.5 h, the constant temperature was 80°C for 1 h, the constant temperature was 120°C for 1 h, the constant temperature was 150°C for 1 h, and the constant temperature was 180°C for 1 h to obtain the coating of this comparative example (F_PAA-ILs coating containing surfactant).

[0278] Comparative Example 7

[0279] This comparative example is a mirror-surface Al sheet with a size of 1.5 cm×1.5 cm×1 mm which is only frosted in Example 2, referred to as Al sheet.

[0280] Comparative Example 8 (the coating of Example 2 does not contain ionic liquid, surfactant and additive)

[0281] The preparation method of the coating of this comparative example comprises the following steps:

[0282] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 30 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved. Then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at -3°C at a speed of 300 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0283] (2) A mirror-finished Al sheet with a size of 1.5 cm×1.5 cm×1 mm was selected as the substrate, and the surface of the substrate was frosted to make the surface of the substrate have a roughness of about 5 μm.

[0284] (3) 0.6 g of F_PAA obtained in step (1) was dropped onto the surface of the substrate after frosting treatment in step (2) to allow it to flow naturally, and then placed in a vacuum drying oven with a gradient temperature increase: the vacuum degree was controlled to be 0.04 MPa, the constant temperature was 50°C for 0.5 h, the constant temperature was 80°C for 1 h, the constant temperature was 120°C for 1 h, the constant temperature was 150°C for 1 h, and the constant temperature was 180°C for 1 h to obtain the coating (Al sheet-F_PAA) of this comparative example.

[0285] Comparative Example 9

[0286] This comparative example is a silicon wafer with a size of 1.5 cm×1.5 cm×1 mm that has only been frosted in Example 3.

[0287] Comparative Example 10 (the coating of Example 3 does not contain ionic liquid, surfactant and additive)

[0288] The preparation method of the coating of this comparative example comprises the following steps:

[0289] (1) Weigh 0.8 g of 2,2′-bis(trifluoromethyl)benzidine (TFDB) and add it to a three-necked beaker, then add 20 mL of dimethylacetamide (DMAc) and stir until the solid powder is completely dissolved, then add 0.7 g of 4,4′-(hexafluoroisopropyl)diphthalic anhydride (6FDA) and continue stirring at 0°C and 400 r / min for 4 h. When the solution adhesion begins to rise to a viscosity of 0.5 Pa·s, stop stirring to obtain a viscous solution of fluorinated polyamic acid (F_PAA).

[0290] (2) A silicon wafer with a size of 1.5 cm×1.5 cm×1 mm is selected as a substrate, and the surface of the substrate is frosted so that the surface of the substrate has a roughness of about 2 μm.

[0291] (3) 0.7 g of F_PAA obtained in step (1) was dropped onto the surface of the substrate after frosting treatment in step (2) to allow it to flow naturally, and then placed in a vacuum drying oven with a gradient temperature increase: the vacuum degree was controlled to be 0.05 MPa, the constant temperature was 50°C for 0.5 h, the constant temperature was 80°C for 1 h, the constant temperature was 120°C for 1 h, the constant temperature was 150°C for 1 h, and the constant temperature was 180°C for 1 h to obtain the coating of this comparative example (silicon wafer-F_PAA coating).

[0292] 2. Performance Test

[0293] 1. Test methods

[0294] (1) Contact angle test

[0295] The contact angle of each embodiment or comparative example coating or substrate (Comparative Examples 1, 7, and 9 are substrates, and all embodiments and other comparative examples are coatings) was measured using a contact angle meter.

[0296] (2) Ice adhesion strength

[0297] Use Figure 3a The homemade ice adhesion strength testing device shown tests the ice adhesion strength.

[0298] like Figure 3aAs shown, the self-made ice adhesion strength test device includes an environment temperature control cabinet 1, an ice column model 3, a stepping push rod 4 and a force sensor. An environment temperature controller is installed on the environment temperature control cabinet 1, and a cooling table 5 is installed at the bottom of the environment temperature control cabinet 1. A cooling table temperature controller for controlling the temperature of the cooling table is installed at the bottom of the environment temperature control cabinet 1; the ice column model 3 is a tubular structure (with an inner diameter of 1 cm and a height of 5 mm); one end of the force sensor can contact the ice column model 3, and the other end is connected to the stepping push rod 4, which is the piston rod of the driving unit 6; the driving unit 6 is installed on the cooling table 5, and the driving unit 6 is one of a cylinder, an electric cylinder or a hydraulic cylinder.

[0299] During the test, the temperature of the cooling table was controlled at -25°C, the temperature of the ambient temperature control cabinet was set at -10°C, the sample 2 was placed on the side surface (upper surface) of the cooling table 5 located in the ambient temperature control cabinet, and the ice column model 3 was placed on the side surface (upper surface) of the sample away from the cooling table 5, and the axis of the ice column model 3 was perpendicular to the side surface (upper surface) of the sample 2 away from the cooling table 5. 1 ml of water was added to the ice column model; it was left for 10 minutes, and after the water cooled and frozen, the stepping push rod carrying the force sensor was adjusted to the section of the ice column model, with the center of the push rod head 1 to 2 mm away from the section, and the height was 1 mm away from the upper surface of the sample.

[0300] Start the test, control the stepping push rod and the force sensor to move at a speed of 0.2mm / s until the icicle causes interfacial shear fracture and moves, stop the push rod, and analyze and calculate the obtained force measurement data. The ice adhesion strength data is obtained by dividing the peak value of the instantaneous force during the fracture process by the frozen area of ​​the icicle (the area of ​​a circle with a diameter of 1cm).

[0301] Among them, sample 2 can be a coating or substrate sample of each embodiment or comparative example (Comparative Examples 1, 7, and 9 are substrates, and all embodiments and other comparative examples are coatings).

[0302] (3) Long-term robustness testing

[0303] Use Figure 3a The homemade extreme low temperature ice adhesion strength testing device shown is used to perform long-term robustness testing on the coatings or substrates of each embodiment or comparative example (Comparative Examples 1, 7, and 9 are substrates, and all embodiments and other comparative examples are coatings). The specific testing method is: using the above-mentioned test steps for ice adhesion strength, the ice adhesion strength of the coatings that have been placed for different days is tested, and the changes in the ice adhesion strength of the coatings over time are observed.

[0304] (4) Self-healing test

[0305] The coating or substrate prepared in each embodiment or comparative example (Comparative Examples 1, 7, and 9 are substrates, and all embodiments and other comparative examples are coatings) with a scratch cut with a depth of 0.3 mm was observed at room temperature (25°C) for 3 hours using a VHX 6000 optical microscope at 300 times magnification and 500 times magnification, respectively, to evaluate the room temperature self-healing performance of the coating or substrate. The specific evaluation method is: if the scratch heals after 3 hours, it means that the coating or substrate has room temperature self-healing performance; if the scratch is basically unchanged, it means that the coating or substrate does not have room temperature self-healing performance.

[0306] (5) Self-cleaning ability test

[0307] Hydrophilic quartz sand and hydrophobic quartz sand are placed on the coating or substrate of each embodiment or comparative example (Comparative Examples 1, 7, and 9 are substrates, and all embodiments and other comparative examples are coatings) to simulate hydrophilic dust and hydrophobic dust respectively, and then water is dripped on the coating or substrate with hydrophilic quartz sand and hydrophobic quartz sand, and a camera is used to observe whether the water can slide off, and whether the coating or substrate has self-cleaning ability is judged based on whether it can slide off. Specifically, if the water can slide off easily and the quartz sand on the surface of the coating or substrate can be easily taken away by the water, it is judged that the coating or substrate has self-cleaning ability; if the water cannot slide off, it is judged that the coating or substrate does not have self-cleaning ability.

[0308] 2. Test results

[0309] The above performance test results of the coating or substrate of each embodiment or comparative example (Comparative Examples 1, 7, and 9 are substrates, and all embodiments and other comparative examples are coatings) are shown in Tables 1, Figure 2 , Figure 4-9 shown.

[0310] Table 1 Performance test results of coatings or substrates in various embodiments or comparative examples

[0311]

[0312]

[0313] According to Table 1, Figure 2 , Figure 4-9 :

[0314] By comparing Examples 1-10 and Comparative Examples 1-10, it can be seen that the ion gel coating of the present application has better hydrophobicity, transparency, long-term robustness, self-repairing performance and self-cleaning ability than the coating or substrate of each comparative example, and has lower ice adhesion strength.

[0315] By comparing Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that compared with the test of directly freezing the FRP sheet without frosting under the same cooling conditions, the ice adhesion strength of the ion gel coating prepared in Example 1 is reduced by more than 99.3%; at the same time, compared with the FRP sheet-F_PAA coating without ionic liquid, surfactant and additive, the ice adhesion strength of the ion gel coating prepared in Example 1 is reduced by about 94.3%.

[0316] By comparing Comparative Example 7, Comparative Example 8 and Example 2, it can be seen that compared with the test of directly freezing on the frosted mirror Al sheet under the same cooling conditions, the ice adhesion strength of the ion gel coating prepared in Example 2 is reduced by more than 98.5%; at the same time, compared with the Al sheet-F_PAA coating without ionic liquid, surfactant and additive, the ice adhesion strength of the ion gel coating prepared in Example 2 is reduced by about 94.1%.

[0317] By comparing Comparative Example 9, Comparative Example 10 and Example 3, it can be seen that compared with the test of ice formation directly on the frosted silicon wafer under the same cooling conditions, the ice adhesion strength of the ion gel coating prepared in Example 3 is reduced by more than 98.2%; at the same time, compared with the silicon wafer-F_PAA coating without ionic liquid, surfactant and additive, the ice adhesion strength of the ion gel coating prepared in Example 3 is reduced by about 93.9%.

[0318] By comparing Comparative Example 3 and Example 1, it can be seen that the contact angle of the ion gel coating of the present application is increased by about 42% compared with the cases where no surfactant is added and where a surfactant is added, and the hydrophobicity is greatly improved; at the same time, the 21-day extreme low temperature ice adhesion strength is 13.6 KPa, which is about 46% lower than 25.3 KPa of Comparative Example 3, indicating that the ion gel coating of the present application can maintain low ice adhesion performance for 21 days and has higher long-term robustness.

[0319] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0320] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0321] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A composition, characterized in that The invention comprises fluorinated polyamic acid, ionic liquid, surfactant and additives.

2. The composition according to claim 1, characterized in that The mass ratio of the fluorine-containing polyamic acid, the ionic liquid, the surfactant and the additive is (20-60): (1.5-27): 1: (40-60).

3. The composition according to claim 1 or 2, characterized in that The fluorine-containing polyamic acid includes at least one of a compound having a structure shown in Formula 1, a compound having a structure shown in Formula 2, and a compound having a structure shown in Formula 3: wherein a, b and c are the number of repeating units in the compound of formula 1, the compound of formula 2 and the compound of formula 3, respectively, and / or the number average molecular weight of the compound of formula 1, the compound of formula 2 and the compound of formula 3 are all 20,000-30,000; And / or, the viscosity of the fluorine-containing polyamic acid is 0.1-2 Pa·s.

4. The composition according to claim 1, characterized in that The ionic liquid comprises at least one of imidazolium chloride, imidazolium tetrafluoroborate, imidazolium bis(trifluoromethanesulfonyl)imide, imidazolium trifluoromethanesulfonate, imidazolium acetate and imidazolium hexafluorophosphate; and / or, The surfactant comprises at least one of dodecyl dimethyl ammonium bromide, hexadecyl dimethyl ammonium bromide and 1-dodecyl-2,3-dimethyl imidazolium bromide; and / or, The additive includes at least one of octavinyl cage-type polysilsesquioxane, aniline propyl cage-type polysilsesquioxane, and dodecaphenyl cage-type polysilsesquioxane.

5. A method for preparing the composition according to any one of claims 1 to 4, characterized in that: include: The fluorinated polyamic acid and the ionic liquid are first mixed to obtain a mixed solution; The mixed solution, the surfactant and the additive are mixed for a second time to obtain the composition.

6. The preparation method according to claim 5, characterized in that: The method for preparing the composition further includes the step of preparing the fluorinated polyamic acid; the method for preparing the fluorinated polyamic acid includes: Reacting 2,2′-bis(trifluoromethyl)benzidine with 4,4′-(hexafluoroisopropylidene)diphthalic anhydride in an organic solvent to obtain the fluorine-containing polyamic acid; And / or, the first mixing and the second mixing both include at least one of ultrasonic dispersion, stirring, and grinding.

7. An ion gel coating, characterized in that: A composition comprising the composition according to any one of claims 1 to 4 or a composition prepared by the preparation method according to claim 5 or 6; the fluorinated polyamic acid in the composition is cured to form a fluorinated polyimide; Preferably, the fluorinated polyimide comprises at least one of a compound having a structure shown in Formula 4, a compound having a structure shown in Formula 5, and a compound having a structure shown in Formula 6: Wherein, n, m and k are the number of repeating units in the compound of the structure shown in Formula 4, the compound of the structure shown in Formula 5 and the compound of the structure shown in Formula 6, respectively, and / or the number average molecular weight of the compound of the structure shown in Formula 4, the compound of the structure shown in Formula 5 and the compound of the structure shown in Formula 6 is 10000-30000; Preferably, the contact angle of the ion gel coating to water is 111-121°.

8. A method for preparing an ion gel coating as claimed in claim 7, characterized in that: include: The composition is dripped or coated on the surface of a substrate and then dried to obtain the ion gel coating.

9. The preparation method according to claim 8, characterized in that: When the composition is dropped onto the surface of a substrate, the method for preparing the ion gel coating further comprises the step of allowing the composition to flow naturally before drying; and / or, The method for preparing the ion gel coating further comprises the step of sandblasting or frosting the surface of the substrate before dripping or coating the composition on the surface of the substrate; and / or, The substrate comprises a material suitable for surface sandblasting; and / or, The drying method includes gradient temperature drying under vacuum conditions; and / or, After the drying, the fluorinated polyamic acid is cured to become the fluorinated polyimide.

10. Use of the ion gel coating according to claim 7 as an anti-icing surface, or use of the ion gel coating prepared according to the preparation method according to claim 8 or 9 as an anti-icing surface.

Citation Information

Patent Citations

  • Anti-icing ionic liquid gel film and preparation method therefor

    CN104987803A

  • Modified high-transparency polyimide flexible film and preparation method thereof

    CN112175184A

  • Preparation method of fluorine-containing polyimide film for gas separation

    CN114854060A

  • Increased saturation of ice melting compositions and methods of use

    US20200339851A1